The Comprehending the Meaning on Song Lyrics “There She Goes” through Interpersonal Metafunctions: A Case on Systemic Functional Linguistics - Silalahi, Tiodora Fermiska; Purba, Ridwin; Silaban, Gabriella Clarisa; Purba, Igna Mariana; Marbun, Elisa May Yolanda; Herman, Herman; Tannuary, Arwin (CV. Creative Tugu Pena, 2024)
This article discusses the Interpersonal Metafunction contained in the lyrics of the song Lee Anthony Marvers’ “There She Goes”. And the purpose of this article is to explain the structure of the lyrics of the song